5‐Hydroxytryptamine (5‐HT)‐exacerbated DSS‐induced colitis is associated with elevated NADPH oxidase expression in the colon. Issue 6 (7th December 2018) - Dong, Shizhen; Chen, Menglu; Dai, Faliang; Xuan, Qingxia; Chen, Pan; Feng, Dandan; Gao, Lei; Zhu, Chendi; Chang, Yongchao; Chu, Fong‐Fong; Gao, Qiang
Abstract: Aim: This study investigated the impact of 5‐hydroxytryptamine (5‐HT) on the expression of NOXs in dextran sulfate sodium (DSS)‐induced colitis in mice. Methods: C57BL/6J (B6) mice at 6 to 8 weeks of age were treated with 5‐HT, DSS, or DSS + 5‐HT. After 6‐day treatment, the severity of colitis, infiltration of leukocytes, and messenger RNA (mRNA) and/or protein levels of Nox1, Nox2, Nox4, and Duox2 were analyzed in the colon by real‐time quantitative polymerase chain reaction (qPCR), immunohistochemistry (IHC), and Western blot analysis. The direct effect of 5‐HT on NOX gene and protein expression in HT‐29 colon cancer cells and in U‐937 macrophage cells were determined by qPCR and Western blot analysis. Results: Mice treated with 5‐HT alone did not develop colitis, while those treated with 1.0% DSS or DSS + 5‐HT had mild and severe colitis, respectively. All treated mice had more myeloperoxidase‐positive cells in the colon compared with untreated control mice. Mice treated with 5‐HT or DSS alone had increased Nox2 and Nox4 mRNA and protein levels in the colon determined by qPCR, IHC, and Western blot analysis. These two Nox expressions were even higher in mice treated with DSS + 5‐HT, while the expression levels of epithelium‐localized Nox1 and Duox2 tended to decrease. Additionally, mice treated with 5‐HT alone had elevated Nox1 and Duox2 expression as shown by qPCR and IHC. However, these gene expressions were diminished in DSS + 5‐HT‐treated mice likely due to erosion of epithelium. Furthermore, 5‐HT induced NOX1 and DUOX2 gene and protein expression in HT‐29 colon cancer epithelial cells, whereas induced NOX2 and NOX4 gene and protein expression in U‐937 cells. Conclusion: As 5‐HT induced NOX1 and DUOX2 gene and protein expression in colon epithelial and HT‐29 cells, NOX2 and NOX4 in the infiltrating leukocyte in mouse colon and in U‐937 cells, the exacerbate colitis induced by combined 5‐HT and DSS treatment might be relevant to increased NOX expression in mice colons.